2022
DOI: 10.7189/jogh.12.05048
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality of COVID-19 in Iranian children and youth: A multi-centre retrospective cohort study

Abstract: Background COVID-19 presents as a mild and less severe respiratory disease among children. However, it is still lethal and could lead to death in paediatric cases. The current study aimed to investigate the clinical characteristics of children and young people hospitalized due to COVID-19 in Qazvin-Iran. We also investigated the risk factors of death due to COVID-19 in paediatric cases. Methods We performed a retrospective cohort study on 645 children and young people (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The comparatively high (36%) in-hospital mortality rate among older patients with COVID-19 confirms that frailty is a key prognostic factor for a poor COVID-19 outcome. As a confirmation of this, a recent work reported that since the beginning of the COVID-19 pandemic the in-hospital mortality rate among 645 Asiatic children and young people (ages 0-17) was 2.5% 17 .…”
Section: Discussionmentioning
confidence: 64%
“…The comparatively high (36%) in-hospital mortality rate among older patients with COVID-19 confirms that frailty is a key prognostic factor for a poor COVID-19 outcome. As a confirmation of this, a recent work reported that since the beginning of the COVID-19 pandemic the in-hospital mortality rate among 645 Asiatic children and young people (ages 0-17) was 2.5% 17 .…”
Section: Discussionmentioning
confidence: 64%
“…The frequency of all-cause mortality may be higher when maternal infection occurs much closer to delivery [ 110 ]. Another study found no difference in mortality between nonsevere (0%) versus severe (0.96%) disease among infants admitted to the hospital.10) Comorbidities may be associated with mortality, but it must also be considered that, in the face of congenital anomalies and other significant comorbidities, the cause of death may not always be truly ascribed to SARS-CoV-2 [ 23 , 32 , 111 ]. Deaths among children with MIS-C or MIS-N presentations have been published [ 9 , 46 , 49 , 112 , 113 ].…”
Section: Covid-19 Among Infantsmentioning
confidence: 99%
“…Regardless of the limitations of existing analyses, several themes have emerged. Among children with COVID-19, some 20%–35% are <1 year of age [ 10 , 12 , 78 , 111 , 128 , 129 ]. The rate of hospital admission may be higher for younger infected patients [ 11 , 128 , 130 ].…”
Section: Controversy Regarding Infantsmentioning
confidence: 99%
See 2 more Smart Citations